2007
DOI: 10.1021/cm071364u
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Nonstoichiometry and Ionic Conductivity of Sr3Fe2-xScxO7-δ

Abstract: The substitution of scandium for iron in the Ruddlesden−Popper Sr3Fe2 - x Sc x O7 - δ (x = 0−0.3) system increases tetragonal unit-cell volume and oxygen nonstoichiometry and decreases partial p- and n-type electronic conductivities studied in the oxygen partial pressure range from 1 × 10-20 to 0.7 atm at 973−1223 K. The solubility of Sc3+ corresponds to approximately x ≈ 0.35. The relatively low, temperature-activated hole mobility indicates a small-polaron mechanism of the electronic transport, as for undop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 29 publications
5
44
0
Order By: Relevance
“…Ruddlesden-Popper series, the partial electronic and ionic conductivities tend to decrease when the concentration of rock salt-type (Ln,A) 2 O 2 layers increases; the general trends observed on acceptor doping are similar to those in the perovskite systems (e.g., Refs [134,165,167,168]). If compared to manganite electrode materials, one important disadvantage of perovskite-related ferrites relates to a high chemical expansion, which provides a critical contribution to the apparent TECs due to oxygen losses at elevated temperatures, and may lead to a thermomechanical incompatibility with common solid electrolytes [117,162,176,177].…”
Section: Perovskite-related Mixed Conductors: a Short Overviewmentioning
confidence: 74%
See 2 more Smart Citations
“…Ruddlesden-Popper series, the partial electronic and ionic conductivities tend to decrease when the concentration of rock salt-type (Ln,A) 2 O 2 layers increases; the general trends observed on acceptor doping are similar to those in the perovskite systems (e.g., Refs [134,165,167,168]). If compared to manganite electrode materials, one important disadvantage of perovskite-related ferrites relates to a high chemical expansion, which provides a critical contribution to the apparent TECs due to oxygen losses at elevated temperatures, and may lead to a thermomechanical incompatibility with common solid electrolytes [117,162,176,177].…”
Section: Perovskite-related Mixed Conductors: a Short Overviewmentioning
confidence: 74%
“…These primarily include perovskite-like (Ln,A)FeO 3Àd and their derivatives existing in all Ln-A-Fe-O systems, A 2 Fe 2 O 5AEd brownmillerites, (Ln,A) 3 Fe 5 O 12AEd garnets in the systems with relatively small Ln 3 þ cations, Ruddlesden-Popper series (Ln,A) n þ 1 Fe n O z , and a variety of other intergrowth compounds such as Sr 4 Fe 6 O 13AEd (see Refs [4,8,17,98,134,152,[157][158][159][160][161][162][163][164][165][166][167][168] and references cited therein). However, due to structural constrains and defect chemistry features limiting both ionic and electronic transport, in most cases an extensive iron substitution is necessary to achieve the total conductivity higher than 10-30 S cm À1 and partial ionic conductivity higher than 0.1 S cm À1 at temperatures above 700 K. For B-site-undoped ferrites, the maximum conductivity is characteristic of perovskite-related solid solutions, such as Ln 1Àx Sr x FeO 3Àd , where the highest level of electronic and ionic transport is known for Ln ¼ La and x % 0.5.…”
Section: Perovskite-related Mixed Conductors: a Short Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the developed materials, cobalt-doped Ln x (Ba,Sr,Ca) 1−x Co y Fe 1−y O 3−ı (Ln: rare earth metal, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1) usually have high oxygen permeation fluxes but are unstable under reducing environments and long-term operation at high temperatures [11][12][13][14][15][16][17][18][19][20]. Ln x (Ba,Sr,Ca) 1−x Fe y (Zn,Al,Ga,Ti,Zr,Ce) 1−y O 3−ı (0 ≤ x ≤ 1, 0 ≤ y ≤ 1) usually possesses high stability under reducing environments but poor permeation fluxes [21][22][23][24][25][26][27][28][29][30][31]. Researchers have found that it is difficult to obtain a membrane material with high stability and permeation flux based on perovskite or perovskite-related structures [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…An attractive combination of properties important for these applications, namely a relatively high conductivity, moderate thermal expansion coefficients (TECs), and substantial stability in reducing atmospheres, is known for the Ruddlesden-Popper (RP) type Sr 3 Fe 2 O 7-δ [5][6][7][8][9][10][11][12]. The intergrowth structure of this ferrite ( Fig.…”
Section: Introductionmentioning
confidence: 99%